2nd U.S. Precision Livestock Farming Conference (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue presents a collection of 16 articles extracted from the conference proceedings of the 2nd U.S. Precision Livestock Farming Conference in Knoxville, TN, held May 21–24, 2023. These articles cover a broad range of topics, including sensors and sensing in PLF, data management and algorithm development, the measuring, modeling, and managing of dynamic responses, and the societal impacts of PLF. With their diverse subject matter, these articles serve as an invaluable resource for an array of readers, including researchers, extension practitioners, producers, legislators, manufacturers, and beyond. By delving into the latest advancements in precision livestock farming, readers can gain a deeper understanding of emerging trends and foster collaborations that drive progress within the field. We extend our heartfelt appreciation to the authors who have made significant contributions to this Special Issue.